Incest as a Penal Law Issue (Two Perspectives) (Archives of Criminology, 2008)
The authors of this article touch upon the criminal law aspects of incest and the criminalisation of such practices on the basis of the Polish Penal Code (Daniluk) and the solutions adopted in the following countries: Canada, Australia, the USA, and France (Nowak), while the views that they present are not fully consistent with each other. The first part of the paper outlines the norms of Polish law that regulate the issue of incest. According to Daniluk, the criminalisation of this practice is strongly connected with the protection of moral norms. The definitions of kinship and adoption are also discussed, as well as the issue of incest being understood as a victimless crime. The text touches upon the problems of disclosing and prosecuting such crimes with regard to the voluntariness of the act, as well as of identifying the forbidden act due to the imprecision of Article 201 of the Penal Code. Daniluk also argues that the law adopted in this area does not ensure sexual freedom, but rather limits it and serves only to protect morals. In the author’s opinion, there is doubt whether criminal law can regulate the issues of morality and sexual freedom. The arguments of researchers in the field of genetics are also quoted, showing the consequences for the health of any offspring from incestuous unions, although concerns of eugenics have been ignored by the legislature in the current regulations. The study concludes that the criminalisation of incest serves to protect proper family relations, indirectly taking into account eugenics, but does not constitute the protection of minors. In the second part of the article, Nowak describes the legal status referring to the issue of incest and its criminalisation in the above-mentioned countries. The article also focusses on the definition of incest and the scope of the relationships and persons subject to possible punishment. The author presents justifications for the criminalisation of incest in particular countries on the grounds of eugenics and protecting minors or morality. The author cites the work of committees for decriminalising incest which operate in Canada, Australia, and the USA, stressing that the drafts were rejected in all these countries. In this section, Nowak also discusses the issue of the value of individual freedom colliding with the protection of other values. The author asks to what extent criminal law tools can be used to regulate the sphere of sexual life. In the conclusions, Nowak addresses the problem of legitimacy in raising the argument of eugenics, if it is not applied to other groups and types of relationships where offspring may be burdened with genetic defects. She also raises the issue of to what extent criminal law should regulate family relations and how the public good is protected if the relationships are voluntary between two adults. The author points to the need for changes in the Polish legal system to protect minors in regards to incest as well as a reconsideration of changing the existing criminal law in favour of abandoning the regulation of the sexual freedom of adults.